Psychological Wellbeing of Diabetic Individuals, Prediabetics, and Non-diabetics: A Population-Based Study in Saudi Arabia - Aldossari, Khaled K.; Shubair, Mamdouh M.; Al-Ghamdi, Sameer H.; Alduraywish, Abdulrahman A.; Almeshari, Alhanouf Abdullah; Alrasheed, Abdullah A.; Aldahash, Raed; Angawi, Khadijah; Gaissi, Anood; Alhumud, Hana Abdullah; El-Metwally, Ashraf (Frontiers in Psychology, 2022)
Background: The increased burden of diabetes affects the quality of life, including psychosocial problems. The study aims to compare the psychological well-being of individuals with prediabetes, diabetes, and non-diabetes. Methods: A cross-sectional exploratory study was conducted from January-June 2016 (n = 1019) in Al Kharj, Saudi Arabia. After consent and questionnaire were filled out, trained staff took blood samples followed by anthropometry. Chi-Squared tests, One-way ANOVA, and multiple linear regression analyses examined the association between diabetes classes defined by HbA1c cut-off levels set by the American Diabetes Association (three categories), individual items, and total score of general health questionnaire (GHQ). A ROC curve was plotted for the total GHQ-12 score against HbA1c. Findings: The mean GHQ score for psychological distress was significantly higher (F=6.569, P=0.038) in diabetics (mean = 14.7) and prediabetics (12.4) than in non-diabetics (10.71). four out of six GHQ positive items and three out of six GHQ negative items significantly differed between three diabetes classes. Adjusted multivariate analysis revealed that people with diabetes were most likely to report psychological distress than non-diabetics (unstandardized Beta = 2.414; P = 0.037). The AUC examining the relationship between HBA1c and GHQ scores showed a moderate but statistically insignificant sensitivity/specificity of 0.643 (P = 0.23). Conclusion: This study demonstrates that psychological well-being is substantially poorer among diabetic or prediabetic individuals than non-diabetic individuals. Future longitudinal studies are required to examine plausible causal relationship between diabetes/prediabetes and psychological distress.